PENGARUH KEPUASAN, KOMITMEN, MANFAAT SOSIAL DAN SPECIAL TREATMENT BENEFITS TERHADAP LOYALITAS PELANGGAN - VITA BRILIANA (Jurnal Bisnis dan Akuntansi, 2013)
The purpose of the research is to examine the influence of satisfaction, commitment, social benefits, special treatment benefits and customer loyalty. Data was collected using survey questionnaire distribution to 100 respondents. The respondent of the research is people who buy Kentucky Fried Chicken (KFC) product through delivery order. Data were analyzed using multiple regression analysis. The result showed that there is significant influence of satisfaction, commitment, social benefits, special treatment benefits and customer loyalty.